Alltagsleben und politische Partizipation - Gecekondu-Viertel als gesellschaftlicher Ort - Heidi Wedel (European Journal of Turkish Studies)
This article demonstrates how gecekondus as a specific place pre-structure social space and political participation. Gendered place and gendered space in gecekondus lead to gendered political priorities and action. Housing security is a ‘felt need’ shared by all squatters. Yet regarding infrastructure and social institutions, men focus on the wider city and demand better connection to urban traffic and improved institutions on the district level. On the other hand, women whose social and work life is widely restricted to the neighbourhood, are primarily concerned about deficiencies of infrastructure within the neighborhood. Whereas men may assume formal roles in politics, women are widely excluded from the male-dominated public sphere and related resources of political participation. Their political action is rather based on spatial and social resources of participation such as informal networks, which are facilitated by place and space in gecekondus. Women’s political participation is mainly of an informal nature. The article discusses the effects and constraints of their collective actions regarding political awareness, local leaders and formal political participation.